1997
DOI: 10.1159/000177509
|View full text |Cite
|
Sign up to set email alerts
|

Renal Protection in Diabetes-An Emerging Role for Calcium Antagonists

Abstract: The combination of diabetes and hypertension increases the chances of progressive renal disorder and ultimately renal failure. Roughly 40% of all diabetics, whether insulin dependent or not, develop diabetic nephropathy. Diabetic nephropathy is the single most important cause of end-stage renal disease in the western world and accounts for more than a quarter of all end-stage renal diseases. It is also a major cause of increased morbidity and mortality in diabetic patients. Increased arterial blood pressure is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Calcium-channel blockers may be superior to ACE inhibitors as direct vasodilators to provide the more strict blood pressure control needed to delay progression of nephropathy in patients with complicated DM. In fact, with the exception of the short-acting dihydropyridine agents, a recent analysis shows that most calcium-channel blockers reduce or stabilize glomerular filtration rate in DM [36].…”
Section: Diabetic Nephropathy and Vascular Riskmentioning
confidence: 99%
“…Calcium-channel blockers may be superior to ACE inhibitors as direct vasodilators to provide the more strict blood pressure control needed to delay progression of nephropathy in patients with complicated DM. In fact, with the exception of the short-acting dihydropyridine agents, a recent analysis shows that most calcium-channel blockers reduce or stabilize glomerular filtration rate in DM [36].…”
Section: Diabetic Nephropathy and Vascular Riskmentioning
confidence: 99%
“…pril in patients with nondiabetic proteinuria Ͼ3 g/day [33]. Despite these encouraging results, in view of the There is a high prevalence of hypertension, ranging from 30 to 90%, depending on definitions, in type 2 metabolic milieu and multiple medical problems in the majority of type 2 diabetic patients, findings from other diabetes [29,30]. Despite the magnitude of this health problem, there are only a few long-term studies, lasting patient groups may not necessarily be applicable to the majority of hypertensive type 2 diabetic patients.…”
mentioning
confidence: 99%
“…With smaller BP reductions, proteinuria is either unchanged or has been observed to increase. Although it has been suggested that a lack of consistent beneficial effects on proteinuria may not necessarily indicate a lack of effectiveness for long-term preservation of renal function [44], such interpretations are contrary to the known natural history of treated or untreated proteinuric renal disease [3,5,18•].…”
Section: Effects On Proteinuriamentioning
confidence: 99%